Organic Vegetables Production Management of Farmer Group under Cha-am Cooperative at Nong Sala Subdistrict Cha-am District, Phetchaburi Province - Hussano, Pimwipa; Ditthakit , Parichat; SingKham , Junya (Journal for Developing the Social and Community, 2023)
The objectives of this research were 1) to study the management of organic vegetable production of farmers under the Cha-am Colony Cooperative, Cha-am District, Phetchaburi Province; 2) to study the cost and return of the farmer’s management of organic vegetable production under the cooperative. Cha-am Industrial Estate, Cha-am District, Phetchaburi Province 3) to study the success factors. problems and suggestions in the management of organic vegetable production among farmers under the Cha-Am Cooperative, Cha-am District, Phetchaburi Province. This research is a quantitative and qualitative research. The population used in the study was 50 people involved in organic vegetable production management and marketing of the organic farming group using the total population. Data collection using interview form and group discussion. The quantitative data analysis by descriptive statistics were frequency, mean, percentage, standard deviation. data analysis by data classification composition analysis and qualitative data analysis by analyzing external and internal environmental factors. The results showed that 1) Management of organic vegetable production by farmers under the Cha-Am Cooperative Farmers will produce vegetables according to market demand. Produce a variety of vegetables such as kale, Cantonese, chili, eggplant, Chinese cabbage, green oak, etc., with staff from the cooperative to take care of continuously. Farmers will harvest their produce and deliver them to the Cha-am Cooperative every day. The cooperative will check and attach the barcode. before distributing so that consumers can inspect the source of production 2) Cost and return of the management of organic vegetable production by farmers under the Cha-am Cooperative It can be divided into 2 types, which are open vegetable cultivation and greenhouse cultivation. It was found that the cost of planting in greenhouses was more than 15,000 baht. Most will have a cost of 5,000 - 10,000baht, income returns. It was found that planting in greenhouses yields higher than 20,000 and most open-field plantings generate yields of 15,000 – 20,000 baht per year. 3) Success factors in farmer’s management of organic vegetable production. under the Cha-Am Cooperative The success factors of the organic farming group consist of internal factors such as Farmers have experience growing organic vegetables. have knowledge have a good attitude have a clear target customer group Product planning to meet the needs of consumers fast distribution morality strong family Education and continuous development Quality Control Building Standards External factors include support from the Cha-am Cooperative Limited and the government sector to educate, supervise, inspect and drive the organic agriculture network organization. including awareness of environmental resource conservation and health preservation A common problem in production management is climate. environmental conditions, natural disasters, including